Habitat Partitioning in the Marine Sector of Karst Subterranean Estuaries and Bermuda's Marine Caves: Benthic Foraminiferal Evidence - Cresswell, Jacquelyn N.; van Hengstum, Peter J. (Frontiers in Environmental Science, 2021)
Karst subterranean estuaries (KSEs) are created from the two- and three-way mixing of saline groundwater, rain, and oceanic water in the subsurface on carbonate landscapes, and this hydrographic framework promotes unique physical processes, biogeochemical cycling, and biological communities. Here we provide evidence that the source and quantity of particulate organic matter (POM) that is delivered to the benthos strongly correlates to benthic habitat partitioning in the oxygenated marine sectors of KSEs. A dataset of benthic foraminifera at 128 different locations from several large flooded cave systems in Bermuda were compiled and evaluated against common environmental characteristics (e.g., tidal exposure, substrate particle size, bulk organic matter, C:N, total organic carbon, and δ13Corg). Benthic areas receiving more carbon isotopically depleted organic matter sources (mean 13Corg values less than –23.2‰, C:N ratios >11), most likely from the terrestrial surface and some marine plankton, were dominated by Trochammina inflata, Bolivina spp., and Helenina anderseni. In contrast, benthic areas receiving more carbon isotopically enriched organic matter sources (mean 13Corg values greater than –21.6‰, C:N ratios <10), most likely from marine plankton transported through marine cave openings cave from adjacent coastal waters, were dominated by Spirophthalmidium emaciatum, Spirillina vivipara, Patellina corrugata, and Rotaliella arctica. The benthic foraminifera most distal from any cave entrances were dominated by taxa also known from the deep-sea (e.g., Rotaliella, Spirophthalmidium) in sediment with the lowest bulk organic matter content (mean: 6%), or taxa that prefer hard substrates and are potentially living attached to cave walls (Patellina, Spirillina). While physical groundwater characteristics (e.g. salinity, dissolved oxygen) are expected drivers of benthic ecosystems in KSEs, these results suggest that POM source, quantity, and delivery mechanisms (e.g., groundwater-seawater circulation mechanisms, terrestrial flux) play an important role in benthic habitat partitioning and the spatial variability of biogeochemical cycles in the oxygenated marine sector of KSEs.